Heart rate variability responses to neuromuscular electrical stimulation in intensive care unit-acquired weakness patients: A pre–post observational study - Grace Juillet Samosir; Dewi Poerwandari; Dyah Intania Sari; Bambang Pujo Semedi; Atika Atika (Physical Therapy Journal of Indonesia, 2026)
Background: Intensive care unit-acquired weakness (ICU-AW) is common in critically ill patients, occurring in roughly 25–50% of mechanically ventilated ICU patients and limiting early mobilization. Neuromuscular electrical stimulation (NMES) may provide adjunctive rehabilitation and potentially modulate autonomic function. This study evaluated short-term changes in heart rate variability (HRV) after a five-day NMES course in ICU-AW patients. Methods: One-group pre–post observational study in a tertiary ICU. Bilateral quadriceps NMES was delivered once daily for five consecutive days. Five-minute HRV recordings were obtained before the first session and after the intervention period and were analyzed using Kubios. Outcomes were the root mean square of successive differences (RMSSD), the standard deviation of normal-to-normal intervals (SDNN), and the low-frequency/high-frequency ratio (LF/HF); comparisons used Wilcoxon signed-rank tests. Results: Seventeen patients completed the protocol, and no clinically significant NMES-related adverse events occurred. RMSSD increased from 22.49 ms (4.22–93.10) to 51.63 ms (3.81–92.88) (p = 0.010), and SDNN increased from 28.85 ms (11.03–93.54) to 47.70 ms (9.52–137.70) (p = 0.040). The LF/HF ratio showed no significant change (0.65 [0.19–8.24] vs 0.98 [0.18–7.71]; p = 0.190). Conclusion: In ICU-AW patients, a five-day bilateral quadriceps NMES protocol was feasible and well-tolerated. The intervention period was accompanied by higher RMSSD and SDNN, indicating increased beat-to-beat and overall HRV that may reflect greater short-term autonomic adaptability during critical illness.